2020
DOI: 10.3389/fphys.2020.00065
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Serum-Based Metabolic Feature and Characteristic Metabolites in Paraquat Intoxicated Mouse Models

Abstract: Paraquat (PQ) is a widely used herbicide which can cause high mortality to humans. However, relatively few studies focus on metabolic feature of PQ intoxication for investigating the underlying mechanisms. Here we performed non-targeted metabolomics profiling of serum samples from acute and chronic PQ intoxicated mouse models by gas chromatography time-of-flight mass spectrometry (GC-TOF/MS) to identify metabolic feature and characteristic metabolites of acute and chronic PQ intoxication. Results showed that 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Deng et al reported that 14(15)-epoxyeicosatrienoic acid (14(15)-EET) and 19 (20)-epoxydocosapentaenoic acid (19(20)-EDP), the major epoxide metabolites of arachidonic acid (ARA) and docosahexaenoic acid (DHA), respectively, had contrasting effects on kidney injury in a mouse model of ischaemia/reperfusion-(I/R-) induced AKI. Specifically, 14 (15)-EET mitigated and 19 (20)-EDP exacerbated I/R kidney injury [30]. Moran et al demonstrated that cytochrome P450-mediated epoxidation of linoleic acid in a rabbit renal proximal tubule model produced biologically active metabolites that resulted in acute renal failure [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deng et al reported that 14(15)-epoxyeicosatrienoic acid (14(15)-EET) and 19 (20)-epoxydocosapentaenoic acid (19(20)-EDP), the major epoxide metabolites of arachidonic acid (ARA) and docosahexaenoic acid (DHA), respectively, had contrasting effects on kidney injury in a mouse model of ischaemia/reperfusion-(I/R-) induced AKI. Specifically, 14 (15)-EET mitigated and 19 (20)-EDP exacerbated I/R kidney injury [30]. Moran et al demonstrated that cytochrome P450-mediated epoxidation of linoleic acid in a rabbit renal proximal tubule model produced biologically active metabolites that resulted in acute renal failure [31].…”
Section: Discussionmentioning
confidence: 99%
“…The raw data generated by GC-TOFMS were automatically exported to Xplore MET by ChromaTOF software for baseline smoothing and correction, deconvolution, extraction, and alignment of the original chromatographic peak signals, retention index correction, metabolite identification, and data preprocessing (normalization and standardization). Xplore MET software was developed by Metabo-Profile Biotechnology, Inc., based on their published pipeline for GC/MS data processing [13] and has been widely used in dozens of published articles [14][15][16][17][18]. The overall data processing procedure is reliable.…”
Section: Gc-tofms Instrument Settingsmentioning
confidence: 99%
“…The serum sample preparation procedure and GC-TOF-MS analysis were similar to the previously published procedure with slight modification ( Gu et al, 2015 ; Geng et al, 2020 ; Yu et al, 2020 ). In brief, take 50 μl of sample and mix it with 5 μl of internal standard ( L -2-chlorophenylalanine) into 1.5-ml Eppendorf (EP) tubes, and 200 μl of methanol was added.…”
Section: Methodsmentioning
confidence: 99%
“…However, there are some limitations of these methods, which impede the achievement of early monitoring. In recent years, metabolomics, as a new technique, has been used to investigate and describe the overall changes of endogenous small molecular metabolites caused by internal and external stimuli at a specific time and under specific conditions ( Zira et al, 2013 ; Yu et al, 2020 ). It has been widely used in the diagnosis and monitoring of disease progression in the biomedicine field, which provides an important insight into the pathogenesis of the disease ( Dettmer et al, 2007 ; Zhao et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The GC-TOF/MS analysis was performed using a time-of-flight mass spectrometry (GC-TOF/MS) system (Pegasus HT, Leco Corp., St. Joseph, MO,USA),which consists of an Agilent 7890B gas chromatography and a Gerstel multipurpose sample MPS2 with dual heads (Gerstel, Muehlheim, Germany). As described previously [ 26 ], DB-5MS GC column (30 m × 250 μm i.d., 0.25-μm film thickness; Restek corporation, Bellefonte, PA, USA) was chosen for separation. Helium was used as the carrier gas at a steady flow rate of 1.0 mL/min.…”
Section: Methodsmentioning
confidence: 99%